Photoelectric characteristics of silicon P-N junction with nanopillar texture： Analysis of X-ray photoelectron spectroscopy - 刘静 王嘉鸥 伊福廷 吴蕊 张念 奎热西 (Chinese physics B, 2014)
Silicon nanopillars are fabricated by inductively coupled plasma （ICP） dry etching with the cesium chloride （CsCl） islands as masks originally from self-assembly. Wafers with nanopillar texture or planar surface are subjected to phosphorus （P） diffusion by liquid dopant source （POCl3） at 870 ℃ to form P-N junctions with a depth of 300 nm. The X-ray photoelectron spectroscopy （XPS） is used to measure the Si 2p core levels of P-N junction wafer with nanopillar texture and planar surface. With a visible light excitation, the P-N junction produces a new electric potential for photoelectric characteristic, which causes the Si 2p core level to have a energy shift compared with the spectrum without the visible light. The energy shift of the Si 2p core level is -0.27 eV for the planar P-N junction and -0.18 eV for the nanopillar one. The difference in Si 2p energy shift is due to more space lattice defects and chemical bond breaks for nanopillar compared with the planar one.